CLINICAL CASE OF CHRONOTHERAPY OF ARTERIAL HYPERTENSION: FOCUS ON DIASTOLIC BLOOD PRESSURE - Victor, A.; Skokova, N. I.; Petrenko, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
A clinical case of chronotherapy of arterial hypertension (AH) with insufficient blood pressure (BP) night decline has described. Patient P., the BP daily means according to ambulatory BP monitoring (ABPM) was 148/84 mmHg, BP circadian rhythm violation with insufficient degree of nocturnal BP reduction. We recommended the patient to change the mode of antihypertensive drug intake from morning to evening in the same dose. After 3 months complete AH control was achieved with normalization of diastolic BP profile. In the treatment of patients with hypertension it is important not only to achieve target BP levels, but also to restore and maintain its physiological circadian rhythm, including, as the present case reports, DBP. AH control without antihypertensive drugs dosage increase is possible only within chro-notherapeutic approach